Synergy of Environmental Management and Public Policy for Adat-Based Tourism: A Study on the Baduy Cultural Saba, Indonesia - Santoso, Tulus; Nurasa, Heru; Rusli, Budiman; Sumadinata, R. Widya Setiabudi (Journal of Ecohumanism, 2025)
Saba Budaya Baduy in Kanekes Village, Lebak Regency, is a custom-based tourist destination that offers unique culture and beauty of the natural environment. However, the increase in the number of tourists poses new challenges, including environmental degradation, pressure on local culture, and less than optimal public policies in support of sustainability. This study aims to analyze the synergy between environmental management based on local wisdom and public policy in realizing sustainable tourism in the region. The method used is a qualitative approach with case studies. Data was collected through in-depth interviews, field observations, and analysis of policy documents. The results of the study show that the local wisdom of the Baduy indigenous people, such as the prohibition of the use of modern technology and nature conservation practices, plays an important role in maintaining environmental balance. However, the public policies implemented are often not in harmony with customary values, thus creating challenges in destination management. This research identifies the need for closer synergy between the government, indigenous peoples, and tourism actors to create inclusive and adaptive policies. The main recommendations include increasing the participation of indigenous peoples in the policy formulation process, strengthening environmental regulations, and educating tourists about the importance of respecting local customs and the environment. This research is expected to be a reference in the development of other customary-based tourism destinations in Indonesia.